2012
DOI: 10.1159/000345460
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease in Patients with Spinal Cord Injuries/Disorders

Abstract: Background and Objectives: Chronic kidney disease (CKD) and spinal cord injury and disorders (SCI/D) are common and costly conditions among Veterans. However, little is known about CKD among adults with SCI/D. Methods: We conducted cross-sectional analyses of Veterans with SCI/D across all VA facilities in 2006. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2 and categorized by standard eGFR strata. eGFR was calculated in two ways: (a) the Modification of Diet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Underrecognition of chronic kidney disease by primary care physicians has been suggested as an important cause of late or absent nephrology referral. 21 A previous study from Norway found that patients with incomplete SCI were least satisfied probably because their physicians do not acknowledge their complicated medical complaints and do not meet the patient's expectations. 22 This survey was, however, not powered to answer whether it makes a difference from where the patients get their information, and there is a lack of published studies on this topic.…”
Section: Hagen and Rekand Management Of Bladder Dysfunction In Sci Pamentioning
confidence: 99%
“…Underrecognition of chronic kidney disease by primary care physicians has been suggested as an important cause of late or absent nephrology referral. 21 A previous study from Norway found that patients with incomplete SCI were least satisfied probably because their physicians do not acknowledge their complicated medical complaints and do not meet the patient's expectations. 22 This survey was, however, not powered to answer whether it makes a difference from where the patients get their information, and there is a lack of published studies on this topic.…”
Section: Hagen and Rekand Management Of Bladder Dysfunction In Sci Pamentioning
confidence: 99%
“…Bladder infections from multiple daily catheterizations may also spread to the kidney. Chronic kidney disease is highly prevalent in the SCI population, with complications that include decreased glomerular filtration rate and renal plasma flow (30,60,73). For the current study, the expression of two proteins indicative of tissue turnover in the kidneys, transforming growth factor-␤ (TGF-␤; a fibrogenic growth factor implicated in the pathogenesis of renal scarring) and cluster of differentiation molecule 11b (CD11b; an adhesion molecule which promotes cellcell adhesion between leucocytes and leucocyte-endothelial cells in inflammation), were assessed to determine whether improved bladder function with LT could also reduce the kidney's susceptibility to post-SCI complications.…”
mentioning
confidence: 99%
“…An excess risk of diabetes may contribute, at least in part, to the increased risk of stroke, heart disease, and kidney disease that occurs after SCI. [9][10][11][12] The current study addresses this question using the cross-sectional Canadian Community Health Survey (CCHS). The objectives of this study were to estimate the prevalence of type 2 diabetes in the SCI population, to compare this risk with a non-SCI population, and to investigate this relationship after controlling for confounders.…”
mentioning
confidence: 99%